Effect of Plastic Mulching on Soil Carbon and Nitrogen Cycling-Related Bacterial Community Structure and Function in a Dryland Spring Maize Field - Sen Wang (MDPI AG, 2021)
Plastic mulching, given its positive effects on temperature and water retention, has been widely used to solve water shortages and nutrient scarcity in rainfed agricultural soils. This practice affects the physical and chemical processes of soil, including carbon and nitrogen cycling. However, research into microbe-mediated carbon and nitrogen cycling in soil with plastic mulching is still limited. In this study, the structures and functions of the soil bacterial community in non-mulched spring maize, plastic-mulched spring maize, and bareland fallow in a dryland field on the Loess Plateau in China were analyzed to explore the responses of microbe-mediated carbon and nitrogen cycling to plastic mulching. Results showed that the richness of soil bacteria was the highest in bareland fallow. Plastic mulching increased the diversity and richness of soil bacteria to a certain extent (p > 0.05), and significantly increased the content of microbial biomass nitrogen (MBN) (p < 0.05). Plastic mulching enhanced the total abundances of carbon and nitrogen cycling-related microbes, exhibiting a significant increase in the abundances of Cellvibrio, Bacillus, Methylobacterium and Nitrospira (p < 0.05). Predicted functional analysis revealed 299 metabolic pathways related to carbon and nitrogen cycling, including methane metabolism, carbon fixation in photosynthetic organisms, and nitrogen metabolism. The number of gene families assigned to carbon and nitrogen cycling-related metabolic pathways was higher in plastic mulched than that in non-mulched spring maize. This study demonstrated that plastic mulching enhances the capacity of carbon and nitrogen cycling, revealing its potential in mediating greenhouse gas emissions in the dryland spring maize fields on the Loess Plateau.